Ubuntu Philosophy and Mandatory Measles Vaccinations for Children - Sarangarajan, Ruach (Religions, 2022)
This is a primarily normative paper that draws on the thinking about friendliness grounded in an Afro-communitarian (Ubuntu) philosophy to argue for measles vaccine mandates for children below 6 years old under the assumptions that measles vaccines are safe for children in this age group, are widely available, and that children in this age-group experiences two-tiered vulnerability. Suppose the ethics of friendliness grounded in this Afro-communitarian philosophy requires us to be friendly to those who are friendly and unfriendly to a proportional degree to those who fail to be friendly. In that case, we are justified in mandating parents and guardians to vaccinate their children. Studies must research the concrete forms that measles vaccine mandates can take in African contexts.